Alleopathic influence of purple nutsedge (Cyperus rotundus L) root exudates on germination and growth of important field - Ameena, M.; Geethakumari, V.L; George, Sansamma (Annals of Agricultural Research, 2016)
Purple nutsedge (Cyperus rotundus L.) asserts allelopathic effects on crop plants through inhibition of germination, growth or metabolism. Under field conditions, the deleterious effects are facilitated by root exudates, leachates from decomposing residues and residues incorporated into the growing medium. In the present study, laboratory experiments were carried out to investigate the allelopathic influence of nutsedge root exudates collected at different growth stages of weed on seedling growth of rice, cowpea, sesamum, okra and brinjal. The study revealed that the nutsedge root exudates collected at sprouting stage inhibited the germination and growth of all the crop seeds tested. However the exudates collected at later stages did not elicit any response on growth characters of crop seeds. Significant reduction in vigour index was observed in sesamum and okra indicating that nutsedge inhibited the growth of associated crops by the production of inhibitory substances as root exudates. Exudates collected at dormant tuber formation stage caused greatest reduction compared to distilled water treatment. The study indicated that purple nutsedge inhibited the growth of the associated crops like okra and sesamum not only by its competitive nature but also due to the production of inhibitory substances as root exudates